2023
DOI: 10.3389/fpsyg.2023.1168214
|View full text |Cite
|
Sign up to set email alerts
|

A study on the influence of product environmental information transparency on online consumers’ purchasing behavior of green agricultural products

Abstract: IntroductionIn 2020, the outbreak of COVID-19 has forced consumers to shift their consumption patterns online. However, the problem of online fraud in green agricultural products seriously undermines consumer trust and is detrimental to the sustainable consumption of green agricultural products. Therefore, it is particularly important to enhance consumers’ trust in online sellers. This study aims to investigate how the product environmental information transparency(soil information transparency and water infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(83 reference statements)
1
5
0
Order By: Relevance
“…Competence trust will enhance consumers' intentions to purchase, aligning with the findings of Zhao et al [33] and Lu et al [35]. In contrast to the research findings of Fu et al [16], it is observed that the disclosure of environmental information on a product's origin can enhance the benevolence trust among prospective consumers of green food. The disclosure of environmental information about the origins of green agricultural products is significant for consumers who have not yet purchased such products.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Competence trust will enhance consumers' intentions to purchase, aligning with the findings of Zhao et al [33] and Lu et al [35]. In contrast to the research findings of Fu et al [16], it is observed that the disclosure of environmental information on a product's origin can enhance the benevolence trust among prospective consumers of green food. The disclosure of environmental information about the origins of green agricultural products is significant for consumers who have not yet purchased such products.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to Ikhsan et al [52], the act of disclosing information can serve as an effective strategy in mitigating information asymmetry between buyers and sellers in transactions. This practice enables consumers to gain a comprehensive understanding of the production origins and quality of green agricultural products [16], reducing consumers' search costs and fostering an increase in their willingness to make purchases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations